The Empirical Relationship between Stock Return and Trading Volume based on Stock Market Cycles - Christiana, Amanda Melissa; Setiana, Eva; Mamduch, Mamduch (UI Scholars Hub, 2016)
In this paper, we use Markov switching autoregressive model and bivariate VAR model to analyze the empirical relationship between stock return and trading volume based on stock market cycles. Using daily data for the IHSG closing price and trading volume from 2010 to 2014, we identify the bull and bear phases in Indonesia stock market, then we analyze the return–volume relationship in both contemporaneous and dynamic context. We find that (1) there is a positive contemporaneous return–volume relationship in both bull and bear markets, which is only significant in bull markets; (2) no evidence of asymmetry in contemporaneous relationship is found; and (3) there exists a positive unidirectional causality from stock return to trading volume. In addition, our findings are robust for different sample period and data frequency.